If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-7b + 2b + -3)(5b + -2b + 4) = 0 Reorder the terms: (-3 + -7b + 2b)(5b + -2b + 4) = 0 Combine like terms: -7b + 2b = -5b (-3 + -5b)(5b + -2b + 4) = 0 Reorder the terms: (-3 + -5b)(4 + 5b + -2b) = 0 Combine like terms: 5b + -2b = 3b (-3 + -5b)(4 + 3b) = 0 Multiply (-3 + -5b) * (4 + 3b) (-3(4 + 3b) + -5b * (4 + 3b)) = 0 ((4 * -3 + 3b * -3) + -5b * (4 + 3b)) = 0 ((-12 + -9b) + -5b * (4 + 3b)) = 0 (-12 + -9b + (4 * -5b + 3b * -5b)) = 0 (-12 + -9b + (-20b + -15b2)) = 0 Combine like terms: -9b + -20b = -29b (-12 + -29b + -15b2) = 0 Solving -12 + -29b + -15b2 = 0 Solving for variable 'b'. Factor out the Greatest Common Factor (GCF), '-1'. -1(12 + 29b + 15b2) = 0 Factor a trinomial. -1((4 + 3b)(3 + 5b)) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(4 + 3b)' equal to zero and attempt to solve: Simplifying 4 + 3b = 0 Solving 4 + 3b = 0 Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3b = 0 + -4 3b = 0 + -4 Combine like terms: 0 + -4 = -4 3b = -4 Divide each side by '3'. b = -1.333333333 Simplifying b = -1.333333333Subproblem 2
Set the factor '(3 + 5b)' equal to zero and attempt to solve: Simplifying 3 + 5b = 0 Solving 3 + 5b = 0 Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5b = 0 + -3 5b = 0 + -3 Combine like terms: 0 + -3 = -3 5b = -3 Divide each side by '5'. b = -0.6 Simplifying b = -0.6Solution
b = {-1.333333333, -0.6}
| 5x+1=3x+29 | | (6-3*3)-7= | | 2a+4b-2a-b= | | 0=6s^2-11s+4 | | (a+2a+5)(a-3a-7)=0 | | 0=6s^2+11x-4 | | 5(2T-2)=20 | | 15k^2-7k=4 | | -42+2x=22-6x | | (x-7x+4)(2x-3x-6)=0 | | (6x+4)+2x-16=180 | | (5x-2)(7-5x+2x)=0 | | 5+2d=29 | | 11j=6j-5 | | .17*1.2= | | 27=4x+7 | | (4s+5)(3s+8s-9)=0 | | 3c+4=11 | | 9x-5x^2=-2 | | 3+4=11 | | (x-2)(x+2x+4)=0 | | 9k-4=23 | | p+2=9 | | 3c+7=10 | | 2(m-3)(m-3)+2m^2+12m=-3m^2+5 | | 18+7x(32-16)= | | 4(d-9)+3(2d+8)=32 | | 6v-=42 | | 5=13-k | | (w+2)(w+2)-2(w+2)+9w=8 | | (5r-7s)(4r+3s)=0 | | .67(6h+3)=.33(3h-4)-h^2 |